Descending Transcendence - Peers, Glenn (Religion and the arts, 2018)
AbstractThis essay argues for the importance of stuff for understanding human significance and humility. It examines a number of contemporary artists' work in the motile miniature, the scale of transcendence that suits both our relation to the world surrounding us and to that below our habitual perception. The transcendence proposed is not vertical and anagogical, but downward toward the level of the minute, even molecular, where we can find the vitalist forces of the world, and our own responsibilities and roles within them. This essay takes as it subject several projects by modern and contemporary artists, in order to argue for why matter matters. Each follows the route to transcendence through descent that was first recorded in the method of Thales of Miletus in archaic Greece, when he went below ground for a wormworld view into the heavens so that he could see the stars more clearly. Each of these artists allows us to enter into the perspective of stuff that might push against our insistence on human priority and open to a different level of sublime.